Solid Solutions of LiCo1−xNixO2 (x=0, 0.1, …, 0.9) Obtained via a Combustion Synthesis Route and Their Electrochemical Characteristics. (11th February 2013) - Elong, Kelimah; Kamarulzaman, Norlida; Rusdi, Roshidah; Badar, Nurhanna; Jaafar, Mohd Hilmi
Abstract : Pure, single-phase and layered LiCo 1 − x Ni x O 2 materials with good cation ordering are not easy to synthesize. In this work, solid solutions of LiCo 1 − x Ni x O 2 ( x = 0, 0.1, …, 0.9) are synthesized using a self-propagating combustion route and characterized. All the materials are observed to be phase pure giving materials of hexagonal crystal system with R-3m space group. The RIR and R factor values of stoichiometries of LiCo 1 − x Ni x O 2 ( x = 0.1, 0.2, 0.3, 0.4, and 0.5) show good cation ordering. Their electrochemical properties are investigated by a series of charge-discharge cycling in the voltage range of 3.0 to 4.3 V. It is found that some of the stoichiometries exhibit specific capacities comparable or better than those of LiCoO2, but the voltage plateau is slightly more slopping than that for the LiCoO2 reference material.